Finding neighbors [videorecording (DVD)] - Judkins, Ron; O'Keefe, Michael, 1955-; Dent, Catherine; Bashoff, Blake (Strand Releasing Home Entertainment, 2015)
Sam Tucker, a successful stay-at-home graphic novelist, has hit a mid-life and creative crisis. Six months late on the deadline of his latest novel, Sam has already created turmoil with his publisher after his last book was a disaster. When his therapist wife Mary suspects Sam of having an affair with Sherrie, his provocative next-door neighbor, she is surprised to find out he's actually spending time with the other next-door neighbor, Jeff, a gay fellow 'househusband'.